Individualizing English Learning: Implementing Differentiated Instruction - Diananseri, Chanti; Yaslina, Ravica (Asosiasi Ide Bahasa Kepri, 2024)
This study is intended to investigate the approaches employed by teachers in instructing English through differentiated instruction. A case study methodology was employed, focusing on three English teachers at SMPN 5 Padang Panjang. Data collection involved conducting interviews and making observations. The data was then analyzed through triangulation. The findings revealed that differentiated instruction involves adapting teaching methods to suit the individual needs of students. This is deemed crucial as it allows teachers to provide multiple avenues for students to comprehend information, addressing the diverse needs present within a classroom. Teachers utilize various strategies, including adjustments in content, process, product, and learning environment, to accommodate these needs while maintaining focus on the same topic. The study suggests that differentiated instruction in English education is grounded in the identification of students' learning needs, typically assessed through initial surveys, pretests, or diagnostic assessments. Subsequently, teachers tailor English instruction based on these assessments. Additionally, teachers conduct both summative and formative evaluations to assess the effectiveness of their instructional strategies